2014
DOI: 10.2337/dc13-1934
|View full text |Cite
|
Sign up to set email alerts
|

Normalizing Metabolism in Diabetic Pregnancy: Is It Time to Target Lipids?

Abstract: Outcomes in pregnancies complicated by preexisting diabetes (type 1 and type 2) and gestational diabetes mellitus have improved, but there is still excess morbidity compared with normal pregnancy. Management strategies appropriately focus on maternal glycemia, which demonstrably improves pregnancy outcomes for mother and infant. However, we may be reaching the boundaries of obtainable glycemic control for many women. It has been acknowledged that maternal lipids are important in pregnancies complicated by diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
124
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(137 citation statements)
references
References 63 publications
8
124
0
4
Order By: Relevance
“…The rising levels of estrogen with the progression of pregnancy reflects the changes in lipoproteins [9]. On the other hand, dyslipidemia increases with the insulin resistance found in obesity, GDM and preexisting diabetes, as it has been extensively researched in the studies of Kitajima et al [10], Knopp et al [14] and Gobi et al [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rising levels of estrogen with the progression of pregnancy reflects the changes in lipoproteins [9]. On the other hand, dyslipidemia increases with the insulin resistance found in obesity, GDM and preexisting diabetes, as it has been extensively researched in the studies of Kitajima et al [10], Knopp et al [14] and Gobi et al [15].…”
Section: Discussionmentioning
confidence: 99%
“…More, but not all studies have reported the same lipid profiles in wellcontrolled DM1 as in normal pregnancies, high triglyceride and low HDL-C are found in DM1 women with metabolic syndrome in pregnancy, and those diabetic women who develop preeclampsia have high LDL-C and cholesterol levels. In pregnant GDM women frequent founding are the elevated triglycerides while in DM2 pregnancies the lipid profiles are between those observed in DM1 and GDM [9,10]. Hence, we decided to explore lipids in DM2 and GDM pregnancies because the latter is a form of type 2 diabetes and they share the same underlying pathophysiology (insulin resistance and beta cell dysfunction).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] Dyslipidemia as the cause of insulin resistance in GDM is still debated as questioned by Helen et al Though HDL levels were statistically insignificant in cases, an increasing trend towards the controls was observed which may be clinically significant. This lack of statistical significance can be substantiated based on the physiological drop in HDL levels in controls as shown in a population based study by Raghuram Pusukuru et al [17][18] Linear correlation analysis revealed a strong linear relation between OGCT and VAI (p <0.0001). VAI was significantly higher in cases compared to controls in parallel with increase in TGL, BMI, waist circumference and decrease in HDL in cases.…”
Section: Figure 1: Age Distributionmentioning
confidence: 99%
“…Despite these findings, postpartum screening for lipid abnormalities and other cardiovascular risk factors has been neglected in women with gestational diabetes (13). In addition, few studies focused on early postpartum lipids profile, particularly in women with GDM.…”
Section: Introductionmentioning
confidence: 99%